Prevalence of sexual harassment among young Spaniards before, during, and after the COVID-19 lockdown period in Spain - Laura Vall-Llosera Casanovas; Laura Serra; Carme Saurina Canals; Belén Sanz-Barbero; Carmen Vives-Cases; Maria José López; Laura Otero-García; Gloria Pérez; Gemma Renart-Vicens (BMC Public Health, 2022)
Abstract Background Sexual harassment is a type of coercion, including social pressure, intimidation, physical force, and verbal acts, in addition to other forms such as cyber-harassment, recognized as a major important public health problem. Methods This cross-sectional study, based on a survey administered online to men and women aged 18 to 35 years and living in Spain throughout 15th and 28th October 2020, aims to analyze the prevalence and factors associated with sexual harassment among young people in Spain within the last 12 months, particularly according to the COVID-19 lockdown period. It has been conducted by bivariate analysis and robust Poisson regression models. The final sample includes 2.515 participants. Results The results indicate that women were almost twice as likely as men to experience sexual harassment (49% vs 22.2%). Also, among heterosexual men and women, the estimated prevalence was lower concerning that observed among bisexuals, gays, and lesbians (31.5% vs 53, 39.2, and 34.6% respectively). The prevalence percentage in the 18–24 age group was twice high as that observed in the 30–35 age group. Finally, during the lockdown period, the harassment through electronic channels increased (32.6% vs 16.5 and 17.8% before and after this period, respectively) and decreased on public roads (22.9% vs 63.4 and 54.4% pre-lockdown and post-lockdown periods, respectively). Conclusion These findings highlight that sexual harassment presents a high prevalence among young people, especially cyber-harassment, and workplace harassment and it is important to be aware that young women are more likely to suffer harassment and even more if they do not have a partner or have LGB orientation. During the lockdown sexual harassment has moved from public spaces to the social network.